PENGARUH ROA, ROE, NPM DAN EPS TERHADAP HARGA SAHAM PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Adita Miftahul Janah; Faridatuz Zahroh; Siti Amaroh (JEM Jurnal Ekonomi dan Manajemen, 2023)
The purpose of this study is to find out how the effect of return on assets (ROA), Return on equity (ROE), Net profit margin (NPM) and Earning per share (EPS) on the stock prices of transportation companies listed on the Indonesia Stock Exchange (IDX). during the 2019-2022 period. The participants in this study are transportation companies that will be listed on the IDX between 2019 and 2022. The population in this study are transportation companies listed on the IDX in the period 2019-2022. This study used a sample using purposive sampling method so that out of 35 companies, 15 transportation companies were found to fulfill the model used as an exploratory test. The analytical method used in this study is multiple linear regression analysis using the SPSS 26 program. The results showed that Return on Assets (ROA) and Return on Equity (ROE) did not significantly influence the stock price of transportation companies. Meanwhile, Net profit margin (NPM) and Earning per share (EPS) have a significant effect on the share prices of transportation companies listed on the IDX for the 2019-2022 period.